KECEMASAN KEHILANGAN HAFALAN ALQURAN PADA HAFIDZ (PENGHAFAL ALQURAN) DITINJAU DARI TINGKAT RELIGIUSITAS - Muslimah Muslimah; Berliana Henu Cahyani (JURNAL SPIRITS, 2014)
Abstract             Intention of this research is know how far dread of loss of memorizing Al-Quran of at hafidz evaluated from level religions. This subject research is one who have memorized the Al-Quran fully and which still complete its memorizing with the amount four people.                Method of data research used in this research is observation and interview the. Technique analyses the data used in research is data collecting, reduce the data, presenting data, trianggulasi, and recapitulating.                Result of data analysis is there are five dimension religions and three dread aspect which emerge the. Subject still out for overcome the existing stress. Five the dimension is religions ideology dimension or confidence with the sub categorize to believe the truth of doctrine. Dimension of practice religion or observance which is with the sub categorize the ritual and adherence. Experience dimension with the sub categorize the natural by sensation and perception of somebody and also essence of God of Dimension of religion knowledge with the elementary category sub- base of conviction. Dimension consequence with the sub categorize the effect of confidence and effect of practice religion. Dread aspect emerge is aspect intellectual, aspect biology or physiological also emotional aspect and behavior. Aspect Intellectual with the hard category sub concentration, orient the past, productivity degradation. Aspect Biology or physiological with the sub categorize the physical dad. Behavioral and Emotional Aspect with the sub categorize fear. Keyword : Religions, dread lose memorizing Alquran